Efektivitas Nutrasetikal sebagai Agen Kemopreventif dalam Melawan Sel Kanker Payudara - Tesya Agustin; Ratna Dewi Puspita Sari (Medula, 2021)
Cancer is the leading cause of death with breast cancer cases that occupies the highest incidence rate in Indonesia. Breast cancer is a growth of abnormal cells in the epithelium of the ducts or lobules of the breast, causing malignancy in the breast tissue. Beacuse the breast cancer is the most common cancer case, so early detection is carried out and accompanied by recommendations for the most effective treatment for confirmed patients. However, some of these therapies trigger unexpected side effects, then a lot of efforts were made to prevent and control the growth of malignant cells in breast cancer. This malignancy can be inhibited by consuming nutraceutical, which is a combination of nutrition and pharmaceuticals. Nutraceutical is a type of food whose nutritional composition has benefits for health, both prevention and treatment of a disease. The chemopreventive components in fruit and vegetables that are classified as nutritional, besides having effect on health, also having the potential for the anti-carcinogen and anti-mutagenic action. The compounds contained in it are able to against cancer cells with minimal side effects. There are many of them such as ginger, turmeric, cruciferous vegetables, soybeans, tomatoes, garlic, black cumin, and pomegranate have potential anticancer action by reducing the growth of cancer cells, inhibiting cell proliferation, and inducing apoptosis of cancer cells. Thus, nutracetical has potential as a chemopreventive agent with various mechanism of action to against breast cancer cells effectively.